Serum Albumin Trend Is a Predictor of Mortality in ICU Patients With Sepsis. Issue 3 (May 2019) - Kendall, Heather; Abreu, Eduardo; Cheng, An-Lin
Introduction: Patients admitted to the hospital with sepsis are 8 times more likely to die than patients with other diagnoses. There is no diagnostic test that clearly identifies the presence of the dysregulated host response that is central to sepsis. Researchers have identified serum albumin as a possible predictor of mortality in a number of critically ill patient populations. However, these studies primarily focus on the levels on admission, neglecting the clinically significant decrease that occurs subsequently. The purpose of this study was to examine the relationship between the trend of serum albumin over time and mortality in adults admitted to the intensive care unit (ICU) with sepsis. Methods: This retrospective, correlational study used existing medical record data. All patients admitted to the ICU at a Midwestern regional medical center with a primary sepsis diagnosis were included in the initial sample. Logistic regression analysis was used to assess the ability of serum albumin to predict mortality. Results: Serum albumin trend, admission serum albumin level, and lowest serum albumin level were significant unique predictors of mortality. The probability of survival decreases by 70.6% when there is a strong negative trend in serum albumin level, by 63.4% when admission serum albumin is ≤2.45 g/dl, and by 76.4% when the lowest serum albumin is ≤1.45 g/dl. Conclusion: Clinicians are encouraged to measure serum albumin levels in patients with sepsis. Low serum albumin levels and a strong negative trend in serial measurements should instigate aggressive monitoring and treatment in this population.